Facial bone fragmentation in blind cavefish arises through two unusual ossification processes - Amanda K. Powers (Nature Portfolio, 2018)
Abstract The precise mechanisms underlying cranial bone development, evolution and patterning remain incompletely characterised. This poses a challenge to understanding the etiologies of craniofacial malformations evolving in nature. Capitalising on natural variation, “evolutionary model systems” provide unique opportunities to identify underlying causes of aberrant phenotypes as a complement to studies in traditional systems. Mexican blind cavefish are a prime evolutionary model for cranial disorders since they frequently exhibit extreme alterations to the skull and lateral asymmetries. These aberrations occur in stark contrast to the normal cranial architectures of closely related surface-dwelling fish, providing a powerful comparative paradigm for understanding cranial bone formation. Using a longitudinal and in vivo analytical approach, we discovered two unusual ossification processes in cavefish that underlie the development of ‘fragmented’ and asymmetric cranial bones. The first mechanism involves the sporadic appearance of independent bony elements that fail to fuse together later in development. The second mechanism involves the “carving” of channels in the mature bone, a novel form of post-ossification remodeling. In the extreme cave environment, these novel mechanisms may have evolved to augment sensory input, and may indirectly result in a trade-off between sensory expansion and cranial bone development.